4500 V SPT+ IGBT optimization on static and dynamic losses*Project supported by the National Major Science and Technology Special Project of China (No. 2011ZX02504-002). (September 2015) - Dai 戴, Qingyun 庆芸; Tian 田, Xiaoli 晓丽; Zhang 张, Wenliang 文亮; Lu 卢, Shuojin 烁今; Zhu 朱, Yangjun 阳军
Abstract: This paper concerns the need for improving the static and dynamic performance of the high voltage insulated gate bipolar transistor (HV IGBTs). A novel structure with a carrier stored layer on the cathode side, known as an enhanced planar IGBT of the 4500 V voltage class is investigated. With the adoption of a soft punch through (SPT) concept as the vertical structure and an enhanced planar concept as the top structure, signed as SPT + IGBT, the simulation results indicate the turn-off switching waveform of the 4500 V SPT + IGBT is soft and also realizes an improved trade-off relationship between on-state voltage drop ( V on ) and turn-off loss ( E off ) in comparison with the SPT IGBT. Attention is also paid to the influences caused by different carrier stored layer doping dose on static and dynamic performances, to optimize on-state and switching losses of SPT + IGBT.